Twenty one years of SBQS (2002 to 2022): A Comprehensive Descriptive and Meta-Scientific Analysis - Carvalho, Luiz Paulo; Lima, Silas; Brandão, Michele; Silva, Mônica Ferreira Da; Oliveira, Jonice; Santos, Gleison; Rocha, Ana Regina (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2023)
As the largest scientific conference in Brazil devoted to software quality, the Brazilian Software Quality Symposium (SBQS) groups and pioneers these area in the country, Brazilian institutions and scholars have advanced software quality since 2002. The goal of meta-research is to investigate, promote, and uphold the integrity of rigorous scientific procedures, comprehending a meta-scientific social and cultural complexity through a diverse and prolific community and scientific activity. We present an analytical-descriptive overview of different SBQS aspects covering all editions, 2002 – 2022, based on data from its publications and derivatives, such as more prolific authorship, institutional collaborations, gender distribution, and abstract analysis. Additionally, we calculate and analyze social network metrics, generating collaboration graphs. SBQS features a connected and involved community, female presences in high production and collaboration positions; there was a predominance of Brazilian Portuguese as the main language until 2017, being surpassed by English in the following years. UFRJ stands out in production and authorship, isolated at the top; in terms of collaboration, UFRJ, UFAM, UNIRIO stand out. SBQS authorship are concentrated mainly in the Southeast region of Brazil. The analysis of the abstracts and keywords shows consistency and cohesion between the primary elements of the event and the publications.